THE RISING BURDEN OF CROHN’S DISEASE IN KASHMIR: CLINICAL TRENDS AND CHALLENGES - Waseem Javid; Qazi Aamir; Showkat A. Kadla; Nisar A. Shah (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background : Crohn's disease (CD) presents a significant diagnostic challenge in developing countries with high prevalence of abdominal tuberculosis, parasitic infestations, infectious diarrheas, and functional gastrointestinal disorders. This study aimed to identify the clinical and epidemiological profiles of patients attending a tertiary care hospital in the Kashmir Valley.Methods: The study was conducted in the Department of Gastroenterology, Government Medical College Srinagar, Jammu, and Kashmir, India. All 86 consecutive newly diagnosed patients aged ≥ 17 years were enrolled over a period of 49 months from December 2019 to January 2024. The demographic characteristics and clinical profiles of the patients were studied.Results: Eighty-six newly diagnosed patients were included. Fifty (58.1%) patients were males and thirty-six (41.9%) were females. The mean age of the patients at diagnosis was 35years. Most common symptom was pain abdomen (39.5%) and referred patients for anemia evaluation (34.9%). A diagnostic delay of more than one year was observed in 34 patients. 52 (60.5%) patients required hospital admission for evaluation and management of complicated CD. Joint involvement (28%) was the most common extra-intestinal manifestation (EIM) followed by skin and oral involvement (23%). Surgical intervention at any point during follow-up was observed in 18% of the patients. Steroids and azathioprine were used in 58(67%) patients, followed by biologicals in 22(25.8%). The most common MONTREAL subtype was A2L1B1 (Age, Location and Behavior). Eighty patients were in remission, two died, and 4 lost to follow-up.Conclusions:.Diagnostic delay is still a big concern, leading to more complicated disease.